Pengaruh Gaya Mengajar Guru, Dukungan Orang Tua dan Kepercayaan Diri terhadap Minat Belajar Siswa - Safitri, Shinta Maulidia; Masnawati, Eli; Darmawan, Didit (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2024)
This study aims to understand the influence of teaching methods such as peer pressure, guidance, and self-awareness on students' learning motivation. This study focuses on the influence of guidance, interpersonal relationships, and self-awareness on students' learning motivation at Wadungasri Elementary School, Waru, Sidoarjo. The research conducted here is quantitative. By using 103 respondents as the research sample, the sampling technique used is a census. The data collection method uses a questionnaire, and statistical analysis is carried out using a statistical approach. The findings of the study indicate that teaching by example, having a supportive community, and having self-awareness have a significant positive impact on students' learning intentions at Wadungasri Elementary School, Waru, Sidoarjo. All of these factors have a significant impact on students' understanding of the factors that influence their desire to learn in a traditional classroom environment. Forming and maintaining students' interest in learning in an educational environment is the level of student self-confidence, teacher teaching, and the persistence of parental support